The influence of perceived organizational support, training and development and employee engagement on employee performance mediated by employee engagement at the director’s office PT XYZ - Dwiputri, Luthfa Jusniar; Wanasida, Albert Surya (Institute of Computer Science (IOCS), 2024)
PT XYZ employees' performance shows a decline of 3.65% from 2022 to 2023 or below the target set by management. This decrease may be caused by increased job demands without an accompanying rise in individual competence and capacity. Based on the 2022 employee engagement survey, as many as 54% of employees feel disengaged with the company and their work. Apart from that, it was found that there was unfair treatment in terms of training intensity. This situation can affect employee performance at PT XYZ. Primary data was collected via a Google Form distributed directly to 484 employees by WhatsApp, resulting in 220 responses. The data was then analyzed using the smartPLS 4.0 program with the partial least squares equation analysis method. The results show a positive of perceived organizational support, training and development, and employee engagement on employee performance. As a mediating variable, employee engagement mediates the relationship between perceptions of organizational support and training and development on employee performance. The study advances theoretical understanding in educational contexts and suggests that PT XYZ can improve employee performance by implementing and continuously refining comprehensive training programs. Future research should include diverse employee groups and additional factors influencing performance. PT XYZ is advised to use these insights to significantly boost employee performance.